2013
DOI: 10.1038/bjc.2013.224
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre external validation of IOTA prediction models and RMI by operators with varied training

Abstract: Background:Correct characterisation of ovarian tumours is critical to optimise patient care. The purpose of this study is to evaluate the diagnostic performance of the International Ovarian Tumour Analysis (IOTA) logistic regression model (LR2), ultrasound Simple Rules (SR), the Risk of Malignancy Index (RMI) and subjective assessment (SA) for preoperative characterisation of adnexal masses, when ultrasonography is performed by examiners with different background training and experience.Methods:A 2-year prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
79
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 30 publications
9
79
0
2
Order By: Relevance
“…In our study we found sensitivity 73.5%, specificity 97.1%, PPV 95.3% and NPV 82% by using RMI of more than 200. In the literature different values were defined for RMI and our results confirmed these studies (Jacobs et al, 1990;Davies et al, 1993;Tingulstad et al, 1999;Manjunath et al, 2001;Anderson et al, 2003;Ma et al, 2003;Obeidat et al, 2004;Yamamoto et al, 2009;Van der Akker et al, 2010;Ashrafgangooei et al, 2011;Van Gorp et al, 2012;Sayasneh et al, 2013;Terzic et al, 2013;Arun-Muthuvel et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…In our study we found sensitivity 73.5%, specificity 97.1%, PPV 95.3% and NPV 82% by using RMI of more than 200. In the literature different values were defined for RMI and our results confirmed these studies (Jacobs et al, 1990;Davies et al, 1993;Tingulstad et al, 1999;Manjunath et al, 2001;Anderson et al, 2003;Ma et al, 2003;Obeidat et al, 2004;Yamamoto et al, 2009;Van der Akker et al, 2010;Ashrafgangooei et al, 2011;Van Gorp et al, 2012;Sayasneh et al, 2013;Terzic et al, 2013;Arun-Muthuvel et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…Patients presenting with at least 1 adnexal mass were eligible for inclusion in the study, and when there was more than 1 mass, the mass with the most complex morphologic characteristics or, in cases of similar morphologic characteristics, the largest one was considered for statistical analysis, as suggested by Sayasneh et al 23 More than 1 adnexal mass was detected in 20 women.…”
Section: Methodsmentioning
confidence: 99%
“…There are several studies that validate classification models for adnexal formations; the best results are obtained using the simple Rules and the Logistic Regression 2 (LR2) model, as well as the IOTA group [24], with different levels of expertise [25]. Offline teaching based on 3D volumes for beginners in gynecologic ultrasound shows good results [26].…”
Section: Commentmentioning
confidence: 99%